The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4269/ajtmh.19-0357
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mayaro Virus from a Venezuelan Patient with Febrile Illness, Arthralgias, and Rash: Further Evidence of Regional Strain Circulation and Possible Long-Term Endemicity

Abstract: Fifty-two febrile patients living in Barquisimeto, Venezuela, were screened for arbovirus infection by virus culture during an outbreak of what was thought to be Zika virus infection. We report identification of Mayaro virus (MAYV) on culture of plasma from one patient, an 18-year-old woman with acute febrile illness, arthralgias, and psoriasiform rash. The strain was sequenced and was found to be most closely related to a 1999 strain from French Guiana, which, in turn, was related to two 2014 strains from Hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…MAYV was identified in plasma samples from five patients. Two of the five cases have been previously reported (Ball et al, 2018;Lednicky et al, 2016), albeit as single cases, with the existence of two other strains noted in another paper (Blohm et al, 2019); the current manuscript combines data for all strains, and provides a unified phylogenetic and molecular clock analysis. In one case, the patient was found to be infected with both MAYV and DENV1 (Lednicky et al, 2016); a second case involved a dual infection with MAYV and CHIKV (Ball et al, 2018).…”
Section: Results and Commentmentioning
confidence: 89%
See 2 more Smart Citations
“…MAYV was identified in plasma samples from five patients. Two of the five cases have been previously reported (Ball et al, 2018;Lednicky et al, 2016), albeit as single cases, with the existence of two other strains noted in another paper (Blohm et al, 2019); the current manuscript combines data for all strains, and provides a unified phylogenetic and molecular clock analysis. In one case, the patient was found to be infected with both MAYV and DENV1 (Lednicky et al, 2016); a second case involved a dual infection with MAYV and CHIKV (Ball et al, 2018).…”
Section: Results and Commentmentioning
confidence: 89%
“…Methods for viral identification and phylogenetic analysis have been previously described ( Blohm et al, 2019 ; Mavian et al, 2017 ; Ball et al, 2018 ; Lednicky et al, 2016 ). In brief: plasma was separated and screened by rtRT-PCR for dengue, chikungunya, and zika viruses, with virus isolation then attempted in cell culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAYV was isolated for the first time from the sera of forest workers in Trinidad and Tobago in 1954 [ 3 ]. Since then, several studies have revealed increasing activity of this virus in different Latin American countries, including Brazil, Peru, French Guiana, Ecuador, Bolivia, Colombia, Venezuela, Haiti, Panama, and Trinidad and Tobago [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…MAYV was isolated for the first time from the sera of forest workers in Trinidad and Tobago in 1954 [3]. Since then, several studies have revealed an increasing activity of this virus in different Latin American countries, including Brazil, Peru, French Guiana, Ecuador, Bolivia, Colombia, Venezuela, Haiti, Panama and Trinidad and Tobago [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%